2017
DOI: 10.5812/ijcm.8173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on Fatty Acid Synthase Expression and Enzyme Activity in Breast Cancer Cell Line SKBR3

Abstract: Background: Fatty acid synthase is a multifunctional protein that catalyzes de novo synthesis of long-chain fatty acids. FASN expression is higher in HER2-positive cells, such as SKBR3 and MCF-7/HER2 cells, than in MCF-7 cells, which express lower HER2 levels. Curcumin, a yellow-colored hydrophobic polyphenol derived from the rhizome turmeric, significantly suppressed growth of human breast cancer cells. In this study, we assessed the effect of curcumin on expression and activity of fatty acid synthase in SK-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This inhibition was associated with the regulation of AKT phosphorylation, Bax, and Bcl-2 protein expressions [ 204 ]. FAS inhibition–mediated apoptosis was also reported in curcumin-treated SKBR-3 cells [ 205 ]. Moreover, Tafazzin (TAZ) and Yes-associated protein (YAP) are the key effectors of the Hippo signaling pathway.…”
Section: Curcumin: Impacts On Multiple Cellular Signaling Pathways In Hormone-independent Breast Cancermentioning
confidence: 83%
“…This inhibition was associated with the regulation of AKT phosphorylation, Bax, and Bcl-2 protein expressions [ 204 ]. FAS inhibition–mediated apoptosis was also reported in curcumin-treated SKBR-3 cells [ 205 ]. Moreover, Tafazzin (TAZ) and Yes-associated protein (YAP) are the key effectors of the Hippo signaling pathway.…”
Section: Curcumin: Impacts On Multiple Cellular Signaling Pathways In Hormone-independent Breast Cancermentioning
confidence: 83%
“…Curcumin also down-regulated the transcription levels of Cd36, Srebf1 and Fasn, and up-regulated the transcription levels of Ppara and HSL in IUGR rats. Previous studies indicated that curcumin could suppress the gene expression of Fasn (42) and activate protein expression of PPARα (43) . According to the results of the present study, we could confirm that curcumin could promote lipolysis and fatty acid oxidation in the liver of IUGR rats.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, resveratrol induces apoptosis in the cancer stem-like cells through suppression of FA synthesis by modulating the expression of FASN . Amentoflavone and catechin gallate derivatives (including EGCG, epicatechin gallate, and catechin gallate) have also anti-FASN activity both in vitro and in vivo . Osthole and amentoflavone downregulate FASN and human epidermal growth factor receptor 2 (HER2) protein expression in HER2 overexpressing cancer cell lines. , Capsaicin, curcumin, tannic acid, and primisterin inhibit FASN expression and its activity in different cancers. EGCG inhibits FASN activity and induces apoptosis in breast cancer without inducing weight loss in animal models . Likewise, several flavonoids such as luteolin, quercetin, kaempferol, taxifolin, and baicalein were identified as inhibitors of FASN activity, with the first three compounds being most potent .…”
Section: Phytocompounds Inhibiting Metabolism Of Cancermentioning
confidence: 99%